Experimental analysis of the thermal entrainment three dimensional effects in re-circulated air curtains - Gaspar, Pedro Dinis (2007)
The application of air curtains devices to HVAC&R systems have been developed in order to improve the thermal and mass separation between two contiguous spaces with differentiated air behaviours. The refrigeration equipments installed inside commercial spaces and open to the surroundings suffer alterations of their thermal behaviours and energy efficiency due to variations in magnitude and orientation of the air velocity. The location of the air conditioning system discharge grilles, the mass flows rates originated by pressure differences due to openings to the external environment and the air flow perturbation due to the circulation of the consumers nearby the opening of the display cases, among others, affect the re-circulated air curtain behaviour and the overall performance of the equipment.This study presents the experimental results obtained from tests carried out for the climatic class n.º 3 of EN 441 (Tamb = 25 ºC, φamb = 60%; vamb = 0,2 m/s) and the analysis of the threedimensional effects observed in the thermal interaction through the air curtains installed in open vertical refrigerated display cases. The obtained results are related to the air temperature, air relative humidity and air velocity measurements fields throughout the air curtain. From the analysis of the obtained results some comparable effects in the fields of the same properties for the display space of the exposition and conservation of food products and nearby the inlets/outlets of the air mass flow, can be sorted out. The evaluation of the ambient air velocity three-dimensional effects in the pattern of this type of turbulent air flow is obtained. Additionally, it is verified that the longitudinal airflow fluctuations and the length extremity effects of the display case have a considerable influence in the overall thermal performance of the equipment. The non-uniform distribution of the air temperature, relative humidity and velocity throughout the air curtain determines temperature differences in the linear dimension display space and inside the food products, affecting the correct behaviour of the display cases. Besides that, this study helps to show some of the fragilities of the numerical models bi-dimensional formulation.